AUSTRALIA AND JAPAN INCREASE COOPERATION IN BILATERAL DEFENCE IN RECEIVED ACCESS PACT AGREEMENTS - Fauziah Firdaus Hanim; Yumetri Abidin; Irma Indrayani (Universitas Nasional, 2023)
The Mutual Access Pact agreement, formed between Japan and Australia, aims to enhance bilateral defence cooperation and facilitate joint military operations and exercises, further strengthening defence relations between the two nations. This legal framework enables Japanese and Australian troops to visit each other's territories and engage in joint military activities. Amid China's influential economic growth in the Asian region, Japan sought to bolster its relationship with Australia. This study employs a qualitative method to analyze and reinforce information pertaining to the Mutual Access Agreement between Japan and Australia. Through in-depth interviews, document analysis, and content analysis, the study examines the implications and mechanisms of this pact, shedding light on the importance of collaboration in addressing regional security challenges and fostering stronger defence ties between the two countries. The qualitative approach allows for a comprehensive exploration of the perceptions, motivations, and perspectives of key stakeholders involved in the negotiation and implementation of the Mutual Access Pact. By providing nuanced insights into the dynamics of this defence cooperation agreement, this research contributes to the existing body of knowledge on Japan-Australia relations and offers valuable recommendations for enhancing bilateral security cooperation in the face of evolving geopolitical complexities in the Asian region.